Priority questions in multidisciplinary drought research - Trnka, Miroslav; Hayes, Michael; Jurecka, Frantisek; Bartosova, Lenka; Anderson, Martha; Brazdil, Rudolf; Brown, Jesslyn; Camarero, Jesus J.; Cudlin, Pavel; Dobrovolny, Petr; Eitzinger, Josef; Feng, Song; et al. (Inter Research, 2018)
Addressing timely and relevant questions across a multitude of spatio-temporal scales, state-of-the-art interdisciplinary drought research will likely increase in importance under projected climate change. Given the complexity of the various direct and indirect causes and consequences of a drier world, scientific tasks need to be coordinated efficiently. Drought-related research endeavors ranging from individual projects to global initiatives therefore require prioritization. Here, we present 60 priority questions for optimizing future drought research. This topical catalogue reflects the experience of 65 scholars from 21 countries and almost 20 fields of research in both natural sciences and the humanities. The set of drought-related questions primarily covers drought monitoring, impacts, forecasting, climatology, adaptation, as well as planning and policy. The questions highlight the increasingly important role of remote sensing techniques in drought monitoring, importance of drought forecasting and understanding the relationships between drought parameters and drought impacts, but also challenges of drought adaptation and preparedness policies.
Keywords: Drought Climatology; Climate change; Drought monitoring; Drought forecasting; Drought adaptation; Drought planning; Drought mitigation